2021
DOI: 10.3390/cancers13040612
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Senescence and Implications for the Treatment of Myeloid Malignancies

Abstract: Senescence is a cellular state that is involved in aging-associated diseases but may also prohibit the development of pre-cancerous lesions and tumor growth. Senescent cells are actively secreting chemo- and cytokines, and this senescence-associated secretory phenotype (SASP) can contribute to both early anti-tumorigenic and long-term pro-tumorigenic effects. Recently, complex mechanisms of cellular senescence and their influence on cellular processes have been defined in more detail and, therefore, facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 162 publications
(202 reference statements)
0
1
0
Order By: Relevance
“…Most studies have found that TL is shorter in AML patients compared to the general population [ 25 , 26 ]. Shortened TL in AML patients was closely associated with prognosis and survival [ 27 ]. Additionally, some studies have observed that longer TL was linked to an increased risk of developing AML, which aligned with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have found that TL is shorter in AML patients compared to the general population [ 25 , 26 ]. Shortened TL in AML patients was closely associated with prognosis and survival [ 27 ]. Additionally, some studies have observed that longer TL was linked to an increased risk of developing AML, which aligned with our analysis.…”
Section: Discussionmentioning
confidence: 99%